ESTUDO PRELIMINAR DAS PLANTAS UTILIZADAS COMO MEDICINAIS NO MUNICÍPIO DE CONDOR, RS, BRASIL - Beuter, Sidiane B.; Beuter, Sidiane B.; Batista, Fabiane S.; Dallago, Sinara; Teixeira, Volnei d. A. (Salão do Conhecimento, 2013)
Resumo